A novel clinical protocol for the greater palatine compression suture: A case report - Mihir Raghavendra Kulkarni; Leena Gangadhar Shettar; Purva Vijay Bakshi; Srinath Lakshman Thakur (Wolters Kluwer Medknow Publications, 2018)
Bleeding from the palatal donor site is a worrisome complication of palatal soft tissue harvesting procedures and leads to considerable stress to both the patient and the surgeon. Several methods to control palatal hemorrhage have been suggested in literature, including a palatal suture, but a precise protocol has not been suggested. The present case report aims to suggest a protocol for the greater palatine compression suture (GPCS). Five patients who experienced profuse bleeding from the palatal free gingival graft donor site were treated with the GPCS. The palatal midline was used as a landmark and the location of the greater palatine foramen was estimated. The suture was placed anterior to the estimated location of the foramen and was passed deep into the palatal tissue with the aim of looping and compressing the vascular bundle. In all the patients, an immediate reduction and arrest of bleeding from the palatal wound was observed with blanching of the soft tissues around the suture. The proposed technique is a predictable method to control palatal hemorrhage and can be used if other less invasive techniques fail to stem the blood flow from an injured palatal vessel.